Environmentally Stable Polymer Gels with Super Deformability and High Recoverability Enhanced by Sub‐5 nm Particles in the Nonvolatile Solvent. Issue 11 (3rd April 2019) - Wang, Qiao; Li, Lefan; Li, Zongjin; Guo, Siyao; Sun, Guoxing
ABSTRACT: It remains challenging to satisfy the combined performances for hydrogels with excellent mechanical behavior, high deformability, and super recoverability under harsh environmental conditions. In this study, we first established a strong polymer network via the crosslinking of polymer chains on the surfaces of sub‐5‐nm calcium hydroxide nanospherulites in ethylene glycol solvent. The organic gel expressed excellent mechanical properties such as a recoverable compressive engineering stress of 249 MPa and an elongation stress of 402 KPa, which was attributed to the uniform nanosized crosslinking structure as characterized by SEM. Moreover, the nonvolatile solvent remained in the gel, meaning that the sample can resist a wide temperature range of −56 to 100 °C without losing the elastic properties. This novel organic gel could provide promising routes to develop the ideal elastic carriers for wearable devices, smart skin sensors, and damping materials. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 713–721 Abstract : By using the nonaggregated sub‐5‐nm spherulite nanoparticles and solvent exchange method, a kind of novel transparent organic gel with super mechanical properties, high recoverability, and excellent environmentally stable performance was synthesized. A series of detailed studies on the mechanism of polymerization, interaction of components, bearing capacities, and mechanical stability in harsh environments were presented. This uniform and stable crosslinking network filled with nonvolatile solvent can fulfill the complex requirements for elastic carriers.